Pengaruh Metode Pembelajaran Ilearning Pada Kelas Independent Study Terhadap Peningkatan Kualitas Pembelajaran Dan Penilaian - Ageng Setiani Rafika; Erick Febriyanto; Fikrah Syafa’ah (UNIVERSITAS RAHARJA, 2019)
Raharja College is one of the Universities that applies a learning method that is quite different, that is, it does not only rely on conventional learning systems where the KBM (Teaching and Learning Activities) is carried out by students and lecturers face-to-face, but also applying e-learning methods. learning or better known as the iLearning Education learning system at Raharja College. In its implementation, several devices are used to support the learning system starting from iDu (iLearning Education) as a media for interaction between Students and Lecturers as well as the Use of iLearning Media (IME) as a media that accommodates learning activities through the iLearning Education method. Then during the course of this method several questions arise about how valid the system is for the quality of the assessment and effectiveness of learning methods where it is deemed necessary to apply a measuring instrument that can measure system validity towards the quality and effectiveness of learning methods at Raharja College especially in the Independent class Study IL101A and IL101C. By using a descriptive method with a research survey approach conducted where the survey conducted found a problem solving that is the procurement of a measuring instrument that can later display historical data with certain categories in terms of the effectiveness of learning can be proven empirically through accurate data.